(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Gold nanoparticles (NPs) have been intriguing scientists for over 100 years. Recently, they have been studied for new applications such as cancer treatment. Although the synthesis of gold nanoparticles is extensively reported, in the majority of cases the methodology is confused and/or not clear. We describe a new synthesis methodology for radioactive gold‐198 NPs. Gold-198 was activated in IPEN IEA-01 nuclear reactor. After that, chloroauric acid (HAuCl4) was formed by dissolving the radioactive gold with aqua regia and performing repeated heating cycles. 0.1 mM HAuCl4 containing 100 μL of 1 M NaOH was prepared in a flask equipped with a reflux condenser. The solution was brought to boil and stirred with a PTFE‐coated magnetic stir‐bar. Then 5 mL of sodium citrate was rapidly added. The reaction turns from light yellow to clear, black, dark purple until the solution attained a wine‐red color (2–3 min). Dynamic light scattering (DLS) confirmed 8 nm particles. The presence of gold‐198 (197.968 g/mol; half‐life: 2.69517; decay mode: β‐; average energy: 1.3723 MeV) was confirmed by an ORTEC HPGe detector. DLS was performed after complete decay confirming the 8 nm diameter maintenance. We were able to achieve radioactive gold‐198 NPs and are performing further studies such as: coating reactions, in‐vitro and in‐vivo studies.